2022
DOI: 10.2169/internalmedicine.8487-21
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Revised Classification Criteria for Systemic Autoimmune Rheumatic Diseases and Their Overlap Syndromes

Abstract: Objective We evaluated the performance of the revised classification criteria for assessing different systemic autoimmune rheumatic diseases and their overlap syndromes. Methods A total of 652 patients with or highly suspected of having systemic lupus erythematosus (SLE), systemic sclerosis (SSc), polymyositis (PM)/dermatomyositis (DM) or rheumatoid arthritis (RA)were included in this study. The 1997 revised American College of Rheumatology (ACR) and the 2019 European L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Nevertheless, the existence of overlap syndromes was established based on the clinicians’ opinions and it was not investigated whether it fulfilled the classification criteria or not, which is another limitation to consider. In a recently published paper with 21% of the lupus patients studied having overlap syndromes, the authors found a very similar sensitivity, which was 82.9% for the 1997 ACR criteria and 92.4% for the 2019 EULAR/ACR criteria [ 8 ]. Overall, in SLE with overlap syndrome, we obtained results with a sensitivity comparable to the original publications, which was at the same time similar to the few results in the published literature to date in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the existence of overlap syndromes was established based on the clinicians’ opinions and it was not investigated whether it fulfilled the classification criteria or not, which is another limitation to consider. In a recently published paper with 21% of the lupus patients studied having overlap syndromes, the authors found a very similar sensitivity, which was 82.9% for the 1997 ACR criteria and 92.4% for the 2019 EULAR/ACR criteria [ 8 ]. Overall, in SLE with overlap syndrome, we obtained results with a sensitivity comparable to the original publications, which was at the same time similar to the few results in the published literature to date in this area.…”
Section: Discussionmentioning
confidence: 99%
“…There was also one that looked at the same criteria in a narrower subgroup, e.g., SLE with a long disease duration [ 7 ]. One publication investigated the effect of revising criteria in different connective tissue diseases (CTDs), in which the newer criteria showed increasing sensitivity [ 8 ]. On the other hand, in the last few years, only a small number of publications have analyzed lupus overlap disease, and none of them have examined the impact of the presence of an overlap disease on the fulfillment of the criteria [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, clinical tests to diagnose SLE or to predict flares have also lagged behind other scientific advances in medicine. In the “omics” era of biomarker discovery via DNA/RNA sequencing, epigenetics, and proteomics, SLE is still largely diagnosed and treated according to clinical classification criteria ( 43 , 44 ). Typical laboratory testing conventionally ordered in the clinic to aid in SLE diagnosis includes anti-nuclear antibodies (ANA), anti-double-stranded DNA antibodies (anti-dsDNA), and complement levels, but these tests have limited sensitivity and specificity ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, clinical tests to diagnose SLE or to predict flares have also lagged behind other scientific advances in medicine. In the "omics" era of biomarker discovery via DNA/RNA sequencing, epigenetics, and proteomics, SLE is still largely diagnosed and treated according to clinical classification criteria, as defined by the American College of Rheumatology (ACR) and the Systemic Lupus International Collaborating Clinics (SLICC) [39,40]. Typical laboratory testing conventionally ordered in the clinic to aid in SLE diagnosis includes anti-nuclear antibodies (ANA), anti-double-stranded DNA antibodies (anti-dsDNA), and complement levels, but these tests have limited sensitivity and specificity [41][42][43].…”
Section: Discussionmentioning
confidence: 99%